RECONSTRUCTION OF δ13C OF CHEMOCLINE CO2 (AQ) IN PAST OCEANS AND LAKES USING THE δ13C OF FOSSIL ISORENIERATENE - Breugel Y.V.; Schouten S.; Ossebaar J.; Damsté J.S.S.; Paetzel M. (My University, 2005)
High abundances of the diaromatic carotenoid isorenieratene derived from photosynthetic green sulfur bacteria (Chlorobiaceae) were found just below the chemocline in an anoxic fjord in Norway, throughout the annual cycle. The stable carbon isotope composition of this carotenoid co-varied with the δ13C of CO2 (aq) and is independent of the CO2 and isorenieratene concentration. This constant isotopic fractionation ɛp of isorenieratene versus CO2, 4 ± 1‰, was subsequently used in the reconstruction of δ13C of CO2 at the chemocline in ancient oceans and lakes. These reconstructions indicate that δ13C of CO2 at the chemocline is often influenced by isotopically light CO2, formed by remineralization of organic matter. This process can, depending on the depth and stability of the chemocline, also effect the isotopic composition of the phytoplankton and, thus, isotopic records of sedimentary inorganic and organic carbon.
Keywords: anoxic fjord; biological carbon isotopic fractionation; fossil isorenieratene; oceanic anoxic event; hotosynthetic green sulfur bacteria; δ13C